Aspects of the International Monetary System: International Reserves and International Exchange Rate Regimes - Ingimundur Fridriksson (Norges Bank, 2010)
The global economy has in recent years been characterized among other things by large imbalances between countries and regions, capital flow volatility, and large reserve accumulation by several countries, in some cases well beyond any reasonable measure of reserve adequacy. The global imbalances were most clearly reflected in large current account deficits in the US and large current account surpluses in many emerging market economies in Asia and elsewhere. The surpluses were in at least some cases the result of aggressive export oriented policies and limited exchange rate flexibility. Persistent large imbalances are themselves a potential source of disruptive developments, and the policies of the largest reserve accumulators are likely to have played a role in creating the conditions that brought about the global financial crisis. The report of a high level EU group of experts concluded among other things that -credit expansion in the US was financed by massive capital inflows from the major emerging countries with external surpluses, notably China. By pegging their currencies to the dollar, China and other economies such as Saudi Arabia in practice imported loose US monetary policy, thus allowing global imbalances to build up. Current account surpluses in these countries were recycled into US government securities and other lower-risk assets, depressing their yields and encouraging other investors to search for higher yields from more risky assets. In this environment of plentiful liquidity and low returns, investors actively sought higher yields and went searching for opportunities. Risk became mis-priced.
hdl:11250/2507751
Keywords: 330